The Effect of Foot Reflexology on the Quality of Life of Postmenopausal Women - Fatemeh Mahdavipour; Zohreh Sadat; Neda Mirbagher-Ajorpaz; Mahboobeh Kafaei-Atrian (Journal of Client-centered Nursing Care, 2022)
Background: Menopausal women experience unpleasant physical and mental symptoms that adversely affect their quality of life (QoL). The aim of this study was to investigate the effect of foot reflexology on the QoL of postmenopausal women. Methods: This quasi-experimental study was performed on 90 postmenopausal women who were referred to comprehensive health centers in Yazd, Iran. The subjects were randomly allocated to two equal groups: intervention and control. The intervention group received 15 minutes of foot reflexology on each foot, twice a week for six consecutive weeks. No intervention was performed for the control group. Data were collected through the menopause-specific quality of life (MENQOL) questionnaire. QoL scores were compared between the groups before, immediately after the intervention, and two months after the intervention using Repeated Measures ANOVA. Data analysis was performed using SPSS v. 19. The significance level was set at 0.05. Results: The Mean±SD of the QoL in the intervention group before, immediately after, and two months after the study were 77.44±19.05, 58.02±15.29, and 55.26±12.37, respectively. In the control group, the Mean±SD were 75.71±19.02, 74.82±16.84, and 75.46±18.05, respectively. Using Repeated Measures ANOVA, the comparison of the mean scores of QoL in the intervention group indicated that the scores decreased over time (P<0.001). Conclusion: The results showed that foot reflexology could improve postmenopausal women’s QoL. Due to the simple and easy learning of reflexology, its training is recommended for all menopausal women to improve their QoL.